Upaya Pemerintah Desa Dalam Proses Penyelesaian Hukum Adat Perselingkuhan Suami Isteri Bagi Kehidupan Sosial Masyarakat - Dison, Ronal; Hermanto, Hermanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The location of the research was carried out in Lubuk Mandarsah Village, Tengah Ilir District. This study lasted for 1 month, namely March 01 to March 30, 202. The study aims to determine the government's efforts in the process of implementing the legal settlement of husband and wife infidelity for the social life of the community in Lubuk Mandarsah Village, Tengah Ilir District, Tebo Regency, to analyze the obstacles in the process. implementation of the settlement of the customary law of husband and wife infidelity for the social life of the community in the village of Lubuk Mandarsah, Tengah Ilir District, Tebo Regency and to find out the efforts made by the Traditional Institutions and Syara' employees and the Village Government in overcoming problems in the process of resolving the customary law of husband and wife infidelity in the village of Lubuk Mandarsah, District Tengah Ilir, Tebo Regency. This study uses a qualitative method. The results showed that the process of implementing the legal settlement of husband and wife infidelity for the social life of the community in Lubuk Mandarsah Village, Tengah Ilir District, Tebo Regency, namely: (a) Summoning of the reporting party and the reported party (b) Summoning of witnesses (c) Deliberation process (d) Determination of sanctions . The obstacle in the process of implementing the legal settlement of husband and wife infidelity for the social life of the community in Lubuk Mandarsah Village, Tengah Ilir District, Tebo Regency, namely the shift in values held by the people of Lubuk Mandarsah Village, so that the procedure how should be played by traditional institutions is not widely known and from the disputing family, most of them do not take the case of the affair to traditional institutions or to the village government, but in this case, they take it directly to the police or to the Religious Courts. the community has not been effective and the sanctions for cheating are not in accordance with Islamic law as well as the efforts made by the customary institutions and Syara' employees as well as the village government in overcoming the problem of the process of resolving the customary law of husband and wife infidelity in the village of Lubuk Mandarsah, Tengah Ilir District, Tebo Regency, namely Implementing even more severe sanctions, Conducting socialization, fostering customs and syara' Increasing Human Resources (HR) of Customary Institutions